2011
DOI: 10.1159/000326842
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Evoked Synaptosomal Amino Acid Transmitter Release in Human Brain in Alcohol Misuse

Abstract: Severe chronic alcohol misuse leads to neuropathological changes in human brain, with the greatest neuronal loss in the dorsolateral prefrontal cortex. In this region, GABAA receptors are selectively upregulated, and show altered subunit expression profiles only in alcoholics without comorbid disease, whereas glutamateNMDA subunit expression profiles are selectively downregulated only in alcoholics with comorbid cirrhosis of the liver. To determine whether these outcomes might be conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Such a finding suggests that the basal hyper-glutamatergic state produced by a history of alcohol exposure does not persist into protracted withdrawal, but this requires further investigation within other mesocorticolimbic structures, particularly as functional analysis of glutamate signaling in human postmortem brain tissue indicated higher stimulated glutamate release from dorsolateral prefrontal cortex in alcoholics than in nonalcoholic controls (Kuo & Dodd, 2011). Moreover, akin to findings from studies of alcohol-dependent rats (Zahr et al, 2009), proton magnetic resonance spectroscopy in human alcoholics revealed increases in glutamate in prefrontal cortex (Hermann et al, 2012) and ventral striatum (Bauer et al, 2013) after detoxification.…”
Section: Glutamate Release / Uptakementioning
confidence: 99%
“…Such a finding suggests that the basal hyper-glutamatergic state produced by a history of alcohol exposure does not persist into protracted withdrawal, but this requires further investigation within other mesocorticolimbic structures, particularly as functional analysis of glutamate signaling in human postmortem brain tissue indicated higher stimulated glutamate release from dorsolateral prefrontal cortex in alcoholics than in nonalcoholic controls (Kuo & Dodd, 2011). Moreover, akin to findings from studies of alcohol-dependent rats (Zahr et al, 2009), proton magnetic resonance spectroscopy in human alcoholics revealed increases in glutamate in prefrontal cortex (Hermann et al, 2012) and ventral striatum (Bauer et al, 2013) after detoxification.…”
Section: Glutamate Release / Uptakementioning
confidence: 99%
“…The styryl dye FM2-10 quantifies synaptosome depolarization in vitro Synaptosomes are resealed nerved terminals prepared from fresh brain tissue that contain mitochondria and maintain membrane potential, along with a full complement of receptor and transporter functions 38 . Functional endpoints such as LTP and glucose transport can also be measured in postmortem human synaptosomes, if prepared from tissue that is cryopreserved by mincing and slow freezing in isotonic sucrose [39][40][41][42][43] . In order to verify and quantify depolarization in postmortem AD synaptosomes, we used FM2-10, a styryl dye with a lipophilic tail that becomes fluorescent on insertion into membranes 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…However, most of the studies with electrical stimulation of synaptosomes have applied long lasting (20-30 min) pulses to investigate the metabolic responses of synaptosomes. There is very limited knowledge available regarding the neurotransmission release upon electrical stimulation (Kuo and Dodd, 2011).…”
mentioning
confidence: 99%